Making sense of risk diagnosis in case of prenatal and reproductive genetic counselling for neuromuscular diseases. (March 2014) - Zaccaro, Antonella; Freda, Maria Francesca
This study explored the processes of significance about the risk communication in prenatal/preconception setting within 1 month to the end of genetic counselling intervention. Participants were all attending a programme of Cardiomyology and Medical Genetics in Naples, Italy, for the first time. Transcripts of 18 semi-structured interviews were analysed using interpretative phenomenological analysis. Themes arising included the following: the familiar outcomes of genetic counselling, the risk representation and the impacts on decision-making. The findings suggest the significance of the experience of genetic risk and the implications for the support of individuals and their family after the conclusion of the genetic counselling intervention.